HUBUNGAN KELINCAHAN DAN KOORDINASI MATA DAN KAKI DENGAN KEMAMPUAN DRIBBLING DALAM PERMAINAN SEPAKBOLA PADA TIM PESPI KABUPATEN KUANTAN SINGINGI - Dyyalta Akbar; Slamet Slamet; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study was to determine the correlation of Agility and Coordination of Eyes and Feet with the Dribbling Ability in Football Games on the Pespi Team in Kuantan Singingi Regency. This research belongs to the type of correlational research (Correlation Research). The population of this research is the Pespi Team of Kuantan Singingi Regency with a total of 18 people. From the results of the study obtained the following results: There is a meaningful relationship together between the agility and coordination of eyes and feet with the ability to dribbling where rtab at a significant level α (0.05) = 0.482 means r count (0.634)> rtab (0.482), it means that the Pespi Team in Kuantan Singingi Regency, where rtab is at a significant level α (0.05) = 0.482, means Rhitung (0.634)> rtab (0.482)Key Words: Agility, eye and foot coordination, dribbling